2016
DOI: 10.1039/c5fd00226e
|View full text |Cite
|
Sign up to set email alerts
|

Developing energy efficient lignin biomass processing – towards understanding mediator behaviour in ionic liquids

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Liu et al [ 12 ] found that the stability of the ABTS + was higher in the presence of [Emim]EtSO 4 than [Emim]MeSO 4 , [Emim]Ac, or [Emim]DMP at pH 4.5, which was in accordance with our results. Eshtaya et al [ 34 ] also reported the compatibility of [Emim]EtSO 4 with ABTS + and used them in combination for electrochemical oxidation of lignin. In this work, the contribution of ABTS + scavenging was found to not be a critical factor in LS-induced inhibition; however, it should be taken into consideration when using the laccase/ABTS system for longstanding reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 12 ] found that the stability of the ABTS + was higher in the presence of [Emim]EtSO 4 than [Emim]MeSO 4 , [Emim]Ac, or [Emim]DMP at pH 4.5, which was in accordance with our results. Eshtaya et al [ 34 ] also reported the compatibility of [Emim]EtSO 4 with ABTS + and used them in combination for electrochemical oxidation of lignin. In this work, the contribution of ABTS + scavenging was found to not be a critical factor in LS-induced inhibition; however, it should be taken into consideration when using the laccase/ABTS system for longstanding reactions.…”
Section: Discussionmentioning
confidence: 99%
“…ILs have excellent capability of solubilizing lignin during biomass pretreatment. 45 We expect that laccases and ILs might open the door of sustainable biomass engineering.…”
Section: ■ Conclusion and Future Perspectivesmentioning
confidence: 99%
“…44 Croft and co-workers investigated the mediator behavior in ionic liquids for developing lignin degradation during biomass processing. 45 As already mentioned, laccase-mediated reactions are basically the single-electron oxidation of phenols or amines using molecular oxygen. Since oxygen dissolves well in many ILs, it is expected that ILs are suitable solvents for laccase-catalyzed reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…RTIL have been used for catalytic lignin depolymerisation 30 32 . In addition, the RTIL’s ability to dissolve significant amounts of raw lignin material 33 35 , its thermal stability 36 , promoting free radical reactions 37 and its energy efficiency for biomass processing 38 have promoted RTIL as promising electrolytes for lignin decomposition. Electrochemical decomposition using triethylammonium methanesulfonate as RTIL resulted in conversion rates of 3–6% (w/w) for low cell voltages (1–1.5 V) 39 , but increased to 20% (w/w) near the upper limit of the ionic liquid (1.7 V) 40 .…”
Section: Introductionmentioning
confidence: 99%